Does fear of migrant crime predict xenophobia: Evidence from three Russian cities - Gurinskaya, Anna (European journal of criminology, 2024)
In this study, we examine Russian millennials? attitudes toward migrants?an estimated 10 million legal and four million illegal migrants, who work in construction, service, and retail industries. More specifically, we examine the influence of various factors such as perceived fear of migrant crime, economic, and cultural competition on explaining xenophobia measured by social distance and ethnic exclusionism. Drawing from a survey of 944 university students in St Petersburg, Vladivostok, and Rostov-on-Don, Russia, our findings suggest that fear of migrant crime along with perceived cultural threats are strong predictors of xenophobic attitudes toward migrants. However, the economic threat did not appear to be a strong predictor of xenophobia. Variations existed between cities on dimensions of a perceived threat from migrants, suggesting that geographic and city characteristics are important factors.